Design of interactive learning courseware for data structures - Haifa' Nadhirah Haji Hussain (Nanyang Technological University, 2020)
This report accounts the author’s experience in completing her Final Year Project (FYP) titled ‘Design of Interactive Courseware for Data Structures and Algorithms’, specifically on the topic of Arrays and Linked Lists, and its implementations on Stack and Queue Abstract Data Type (ADT). This report encapsulates the introduction to the project, the overall methodology in developing the courseware for online learning and the process of completing this project. In addition, this report goes into detail the use of Moodle, an open-source learning management system, and the use of Adobe Creative Cloud to create the interactive learning courseware for this project. Lastly, this report will discuss the author’s learning journey, achievements and conclusion to her FYP.